RANCANG BANGUN SISTEM INFORMASI PENYALUR DANA BANTUAN SISWA ( BOS ) BERBASIS WEB - Harfizar Harfizar; Fauzan Manafi Albar; Muh Afiffudin (UNIVERSITAS RAHARJA, 2017)
Application of Information Technology has now spread almost in all fields is no exception in the management of the School Operational Fund allows all operational funds management activities informasi.Kebutuhan technology will utilize information technology is closely connected with the role of fund management boss as a standard program of education that is needed to finance the activities nonpersonnel operation for 1 ( one ) year as part of the overall education funding to education units can conduct educational activities on a regular and ongoing basis in accordance with National Education Standards . With the construction of Management Information Systems Applications